Brigadier Khalil Ibrahim Hussein al-Zobaie and his role in the Ministry of Industry 1967-1968 (Journal of the College of Basic Education, 2022)
The importance of the issue lies in the fact that retired Brigadier General Khalil Ibrahim Hussein is an important figure in contemporary Iraq’s history, as he had a distinguished military, political and intellectual role, if he held many positions, the most important of which was his Minister of Industry on July 10, 1968 until July 17, 1968, when he made many achievements and sought Striving to provide all his expertise in order to improve the industrial reality in Iraq.The role of Brigadier Khalil Ibrahim Hussein in the Ministry of Industry is evident through his experiences in order to develop the industrial reality in Iraq, as if he received his position as Minister of Industry, he did not resort to the management of his ministry in a traditional and routine manner from his office, but he began his career with field visits as he visited many factories The institutions affiliated with the Ministry of Industry to see its workflow and urge it to increase production, and contributed to concluding many industrial agreements with various countries in order to improve the industrial reality of the country that contributed to the exchange of industrial and commercial experiences between Iraq and other countries.